Formulating a Maritime Risk Matrix Based on Ancient Text Quantification: Man-Made versus Natural Risks - Vigih Hery Kristanto; Suharto Suharto; Dyah Purwitasari; M. Anjar Pamungkas (Siber Nusantara Research & Yayasan Sinergi Inovasi Bersama (SIBER), 2026)
Contemporary maritime safety management generally relies on technical approaches, whereas historical analyses can provide a fundamental perspective regarding disaster taxonomy. This research aims to elaborate on the threat weight divergence between human-induced risk variables (Man-Made Risk) and Natural Risk extracted from a corpus of ancient texts, as well as to examine their implications for mapping the ALARP tolerance limits in maritime regulations. This study employs an explanatory quantitative approach integrating computational linguistics with the Formal Safety Assessment (FSA) framework. Ten maritime hazard keywords were converted into absolute numerical units using the Hisab Al-Jummal system of the Masyriqi school, normalized, and calibrated with empirical probabilities to map the Risk Score on a 5×5 matrix. The analysis results prove that Man-Made Risk, specifically the keyword zulm meaning negligence and regulatory violations clearly dominates the hazard hierarchy in the Unacceptable Region with the highest score. Conversely, natural physical threats such as high waves with the keyword mawj have been effectively reduced to acceptable levels due to the standardization of modern ship architecture. The findings indicate prioritize regulatory enforcement that extreme natural conditions essentially act as an initial trigger, while negative human intervention is the primary catalyst for mass maritime tragedies. In conclusion, the results of this study are crucial in encouraging a shift in maritime mitigation strategies so that they do not solely focus on avoiding extreme weather, but rather prioritize regulatory enforcement, regulatory audits, and the strengthening of safety culture.